Preliminary Evaluation of an Automated Blood Cell Analyzer for Its Use with Blood Samples from Rainbow Trout Oncorhynchus mykiss - Montse Mesalles; Meritxell Uroz; Irene Brandts; Emmanuel Serrano; Rafaela Cuenca; Josep Pastor; Mariana Teles (Animals)
Hematological studies provide essential information about the health of animals, which is crucial for veterinary medicine, scientific research, and aquaculture. Automatic hematological analyzers are an alternative to manual methods, offering faster and more reliable results. The objective of this study was to validate the Sysmex XN-1000V automatic hematology analyzer for blood samples from rainbow trout (Oncorhynchus mykiss), examine the effects of two anticoagulants (K2EDTA and lithium heparin), and establish normal blood reference values for this fish species. Additionally, comparative studies were conducted between the Sysmex XN-1000V and manual methods (hemocytometer cell count and blood smear estimation), and reference intervals were established. Ninety-nine heparinized blood samples were analyzed for validation and sample stability tests. The results showed extremely good precision, with a coefficient of variation (CV) below 3% for RBCs, HGB, and HCT and less than 5% for non-RBC cells (leukocytes plus thrombocytes). However, heterophils (%) exhibited higher variability, with a CV of 15.08%. Linearity was excellent, and the carry-over was below 1% for all parameters. The sample stability test indicated that samples could be analyzed for up to 48 h when stored at 4 °C and up to 24 h at room temperature. Non-RBC cells were the first to degrade over time. The automated and manual methods demonstrated good correlation and agreement, validating the analyzer’s accuracy. The effects of two anticoagulants, K2EDTA and lithium heparin, on the blood samples were also studied. Heparin was the preferred anticoagulant for routine hematological analysis of rainbow trout blood with the Sysmex XN-1000V analyzer. In conclusion, the Sysmex XN-1000V enables complete hemogram analyses to be performed quickly and accurately, standardizing techniques, harmonizing results, and providing reliable reference intervals with O mykiss blood.